2018
DOI: 10.1158/1078-0432.ccr-18-0483
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Supplementation and Survival of Patients with Non–small Cell Lung Cancer: A Randomized, Double-Blind, Placebo-Controlled Trial

Abstract: Higher serum 25-hydroxyvitamin D (25(OH)D) levels are reportedly associated with better survival in early-stage non-small cell lung cancer (NSCLC). Therefore, whether vitamin D supplementation can improve the prognosis of patients with NSCLC was examined (UMIN000001869). A randomized, double-blind trial comparing vitamin D supplements (1,200 IU/day) with placebo for 1 year after operation was conducted. The primary and secondary outcomes were relapse-free survival (RFS) and overall survival (OS), respectively.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
64
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 31 publications
1
64
0
2
Order By: Relevance
“…This finding can be attributed to the fact that adenocarcinoma subtype is associated with a poorer prognosis than the squamous cell carcinoma. [19] The decrease in vitamin D levels which is inversely associated with an increase in clinical stage at the time of diagnosis also supports the findings of Wang et al [20] In their study, Akiba et al [21] compared patients with NSCLC who received vitamin D replacement for one year after tumor surgery with the placebo group and found no significant difference than general population in terms of progression-free survival (PFS) and overall survival (OS); however, they observed a significant increase in the PFS and OS rates with vitamin D replacement in the early-stage adenocarcinoma patients. The most recent meta-analysis of 17 prospective cohort studies involving 139,000 patients also suggested that high serum vitamin D levels played a role in the prevention of lung cancer.…”
Section: Discussionsupporting
confidence: 70%
“…This finding can be attributed to the fact that adenocarcinoma subtype is associated with a poorer prognosis than the squamous cell carcinoma. [19] The decrease in vitamin D levels which is inversely associated with an increase in clinical stage at the time of diagnosis also supports the findings of Wang et al [20] In their study, Akiba et al [21] compared patients with NSCLC who received vitamin D replacement for one year after tumor surgery with the placebo group and found no significant difference than general population in terms of progression-free survival (PFS) and overall survival (OS); however, they observed a significant increase in the PFS and OS rates with vitamin D replacement in the early-stage adenocarcinoma patients. The most recent meta-analysis of 17 prospective cohort studies involving 139,000 patients also suggested that high serum vitamin D levels played a role in the prevention of lung cancer.…”
Section: Discussionsupporting
confidence: 70%
“…A similar RCT that included 155 patients found that 1200 IU/d of vitamin D supplementation did not improve relapse-free survival or overall survival of patients with non-small cell lung cancer. 23 However, a meta-analysis of 64 observational studies with a total of 44 165 patients with cancer found higher 25(OH)D levels to be associated with better progression-free and overall survival. 24 In addition, a meta-analysis of individual participant data from 8 cohort studies in Europe and the United States found higher cancer mortality in patients in the lowest quintiles of 25(OH)D levels among people with a history of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Flow diagram of search strategy and trial exclusion with specific reasons is shown in Figure 1. Using predefined search terms, 786 potentially relevant articles were identified, and only ten articles were eligible for inclusion in this meta-analysis [13][14][15][16][25][26][27][28][29][30], corresponding to ten randomized controlled trials and a total of 81362 study participants. All eligible trials reported data on cancer incidence, and seven (including 77653 study participants) of them reported data on cancer mortality.…”
Section: Eligible Trialsmentioning
confidence: 99%